(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The increase in usage of IoT environment is beyond the limits, which use Wireless (WSN).These networks can be used in many environments like logistics, supply chain management,health management,e-governance, smart parking, smart city, and smart appliances. WSN is a collection of sensors spread across them to base station/sink. Remote sensing sensors do sensing of an object remotely and detectthe static or dynamic information.In this paper, discussion is made on how to monitor and track the person’scar within a shopping mall. Remote monitoring and local optimization techniques are used in smart parking architecture, which suits for smart parking environment. Further, description of some of the monitoring and tracking techniques which was used earlier also been discussed with different types of protocols used for this appropriate environment. These systems can be implemented for effective smart parking.